"But if you don't get any IRON..." Towards an Effective Method for Small Iron Smelting Furnaces - Darrell Markewitz (EXARC Journal)
Few ancient processes are as mysterious as smelting ore into metallic iron. Just how, exactly, is this done? The exact processes used by the ancients are unknown, but modern experiments can suggest some possibilities. This essay will concentrate on describing a proven working system, based on Migration Era models, which has repeatedly produced historic type iron blooms. Although labour intensive, the small scale makes this method ideal as a prototype for public demonstrations.